Apexificación en incisivos centrales superiores con biodentine - González Yaguana, Jhannder Jhon (2021)
The present research corresponds to a qualitative, descriptive and documentary literature review, the study was carried out by criteria of exclusion and inclusion, for which several scientific articles based on apexification were analyzed, which aimed to determine the efficacy of Biodentine in the formation of apical closure in permanent upper central incisors, in addition to identifying the properties of this material in relation to dental structures, 26 documentary articles were used in the analysis from 2014 to 2020, bibliographic reviews, clinical cases, which were organized in tables designed for the effect. Apexification is analyzed as a process that allows us to create an environment within the root canal and periapical tissues after pulp death occurs, which allows the formation of a calcifying barrierthrough the open apex. Biodentine is a calcium silicate cement that has biocompatible properties and bioactivity that, when in direct contact with the pulp tissue, induces the development of reparative dentin which manages to maintain the vitality and function of thetissue, in addition, in relation to dental structures, apexification with Biodentine allows an airtight sealing of the dentin tubules in permanent teeth Young permanent teeth, maintaining optimal conditions and correct apical sealing. Keywords: Tooth apex, apexification, pulp necrosis, calcium silicate